The meaning of life in members of Sex and Love Addicts Anonymous, their religious/spiritual activity and the level of happiness - Wnuk, Marcin; Marcinkowski, Jerzy T. (Polish Journal of Public Health, 2011)
Introduction. Sex and love addiction is a significant social problem regarding especially individuals having a tendency to various types of addictions. Like other forms of addiction, sex and love addiction is related to all areas of life, which leads to worsening of the quality of life. The development of the religious/spiritual sphere seems to be a relevant factor for sex and love addicts to recover and improve their quality of life. Aim. The aim of this study was to examine whether the feeling of the sense of life is related to some aspects of religiosity/spirituality and happiness operationalized with global indicators such as the desire to live, passion of life, sense of happiness within the last few days, overall life evaluation, sense of hopelessness as well as the present and anticipated life satisfaction. Materials and methods. The sample comprised 30 participants of Sex and Love Addicts Anonymous (SLAA) fellowships. The following tools were used: the Purpose in Life Test (PIL), Santa Clara Strength of Religious Faith Questionnaire (SCSORFQ), Daily Spiritual Experiences Scale (DSES), Cantril’s Ladder, Beck Hopelessness Scale (BHS), one-item scales concerning the desire to live, passion of life and sense of happiness within the last few days, overall evaluation of life and the frequency of prayer and frequency of Mass attendance. Results. Relationships were observed between the feeling of the sense of life and almost all global measures of happiness, including passion of life, overall life evaluation, the present and anticipated life satisfaction, as well as the sense of hopelessness. The frequency of prayer and strength of religious faith were negative predictors of the sense of hopelessness. The meaning of life mediated between the frequency of spiritual experiences and the sense of hopelessness. Conclusions. The meaning of life is an important factor shaping sex addicts’ sense of happiness. The SLAA members’ spiritual experiences are the source of the sense of the meaning of life.